ANALYSIS OF THE INFLUENCE OF RUPIAH EXCHANGE RATE, BI INTEREST RATE, AND FOREIGN EXCHANGE RESERVES ON INFLATION IN INDONESIA DURING THE PERIOD 2002–2023 - Uskono, Frederina Jubika; Ballo, Fransina W; Tomasowa, Olivia L.E (Jurnal Manajemen Bisnis Dan Organisasi, 2025)
Inflation has long been an economic issue in Indonesia, where this phenomenon is significantly influenced by several factors such as the Rupiah exchange rate, the BI interest rate, and foreign exchange reserves. When maintained at an appropriate level, inflation can stimulate economic growth in a positive direction. The purpose of this study is to analyze the partial and simultaneous relationship between the Rupiah exchange rate, the BI interest rate, and foreign exchange reserves on the inflation rate in Indonesia during the period 2002–2023. This research employs a mixed-method approach, using the Error Correction Model (ECM) for analysis. The data used consist of secondary data in the form of time series, while the primary data were obtained directly from informants through interviews. The partial results indicate that the exchange rate has a significant effect on inflation in both the short and long term; the BI interest rate also significantly affects inflation in both the short and long term. Meanwhile, foreign exchange reserves have a significant effect on inflation in the short term but do not have a significant effect in the long term. Simultaneously, in both the short and long term, the Rupiah exchange rate, BI interest rate, and foreign exchange reserves have a significant effect on inflation in Indonesia.